Social and geographical risk factors in Helicobacter pylori infection. - Whitaker, C. J. (Cambridge University Press, 1993)
A correlation between childhood crowding and the later development of gastric cancer has been demonstrated by Barker and colleagues, who proposed that the relationship was the consequence of infection by an organism such as Helicobacter pylori. In order to test this hypothesis the presence of IgG antibodies to H. pylori in sera from blood donors in North Wales has been investigated. During donation sessions, donors answered questions relating to social conditions and domicile in childhood (at age 10 years) and adult life (the preceding 2 years). A stepwise logistic regression analysis of the data demonstrated significant independent relationships between seropositivity and the following factors: sharing a bed in childhood, housing density, locality of birth, adult social class and age.